Modified bi-crosslinking temperature-sensitive extracellular matrix hydrogel BA / SIS-SC and preparation method thereof
By preparing modified double crosslinked temperature-sensitive extracellular matrix hydrogel BA/SIS-SC, the prevention of anastomosis after colorectal anastomosis was solved, and the structure is stable, excellent biocompatibility and strong antibacterial ability are achieved. The effect significantly improves the healing and safety of the anastomosis.
Patent Information
- Application Number
- CN202411545190.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
Anastomosis leak after colorectal anastomosis is a serious complication. The prior art materials have problems such as poor biocompatibility, high cost and insufficient performance, which are difficult to effectively prevent and treat.
Modified dual crosslinking temperature-sensitive extracellular matrix hydrogel BA/SIS-SC, which forms excellent organisms by combining SIS fragments with 4-ARM-PEG-SC crosslinking agent and processing in boric acid buffer solution Compatibility and mechanical properties of hydrogels.
The hydrogel has a stable structure, good tissue adhesion, anti-explosion ability and self-healing ability, and can effectively block the anastomosis, significantly improve biocompatibility and antibacterial ability, and reduce the risk of abdominal infection.
Smart Images

Figure CN119386245A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives for colorectal anastomosis, and in particular to a modified double-crosslinked temperature-sensitive extracellular matrix hydrogel and a preparation method thereof. Background Art
[0002] Anastomotic leakage is one of the most serious complications after colorectal anastomosis. Its pathogenic factors are complex, the onset is insidious, and it is often complicated by severe abdominal infection, leading to sepsis and even multiple organ failure. With the rapid progress of basic medicine such as molecular biology and pathophysiology, scientists' understanding of the healing mechanism of gastrointestinal anastomosis has deepened from the tissue level to the molecular biology level. Some new methods such as local targeted delivery of growth factors, medical adhesives, and intubation devices have also been gradually applied to the prevention and treatment of anastomotic leakage. However, these methods often have disadvantages such as high cost, poor biocompatibility, and material properties that cannot meet clinical application scenarios, and are not recommended.
[0003] Therefore, there is an urgent need to develop a new type of material that is easy to use and has excellent biocompatibility, anti-digestion, antibacterial and healing properties, which has important clinical value. Summary of the invention
[0004] In order to solve the problem of preventing anastomotic leakage after colorectal surgery, the present invention discloses a modified double-cross-linked thermosensitive extracellular matrix hydrogel and a preparation method thereof. The method successfully prepares a BA / SIS-SC hydrogel with a stable structure and good mechanical and adhesion properties, which can be effectively and safely used to prevent anastomotic leakage.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC comprises the following steps:
[0007] (1) Preparation of SIS fragments: Select intestinal segments, cut them into pieces and sterilize them;
[0008] (2) decellularizing and fragmenting the SIS fragments;
[0009] (3) Preparation of SIS hydrogel;
[0010] (4) Preparation of BA / SIS-SC hydrogel.
[0011] Optionally, in step (1), the specific operation of selecting the intestinal segments, cutting them into pieces and then sterilizing them is as follows:
[0012] Select intestinal segments with complete intestines, uniform thickness and no lymph nodes, and cut them into intestinal segments about 10 cm long; use forceps to peel off the serosal layer and muscular layer, then turn the small intestine over so that the mucosa is outward, use a tongue depressor to repeatedly scrape the mucosal layer to expose the submucosal layer, and use forceps to remove larger tissue particles until no mucosal particles are visible to the naked eye; use sterile PBS buffer to rinse repeatedly to thoroughly remove tissues, cells and cell debris attached to the submucosal layer; cut the tubular submucosal layer along the longitudinal axis on a sterile table, and then use scissors to cut it into pieces <2 mm, soak it in a 20% ethanol solution containing 1.0% peracetic acid for 2 h for disinfection, soak it in a PBS solution containing 0.05% sodium azide for 2 h, and store it in a sterile PBS solution at 4°C for use.
[0013] Optionally, in step (2), the specific operation of decellularizing and fragmenting the SIS fragments is:
[0014] Place the chopped SIS fragments in a -80℃ refrigerator overnight, then place them on ice in a clean bench to reheat and dissolve, repeat twice; after complete dissolution, soak the SIS fragments in 0.1% sodium dodecyl sulfate PBS solution and shake to decellularize for 24 hours; then soak the SIS fragments in 1% DNase I and shake for 12 hours; prepare 1% CHAPS solution and use NaOH to adjust the pH to 7.2-7.4, soak the SIS fragments in CHAPS solution and wash for 48 hours; prepare 1% Triton X-100 solution, soak the SIS fragments in Triton X-100 solution and wash for 30 minutes to thoroughly wash away the cells, and finally rinse repeatedly with deionized water to remove residual reagents; the decellularized SIS fragments are placed in a freeze dryer and vacuum freeze-dried for 24 hours; after drying, the sample is placed in a freeze grinder and ground into powder to obtain SIS freeze-dried particles, and finally sterilized with ethylene oxide and stored in a -20℃ environment for use.
[0015] Alternatively, SIS fragments are soaked in 1% DNase I, SIS(v):DNase I(v)<1:2.
[0016] Optionally, in step (3), the specific operation of preparing the SIS sol is: dissolving pepsin in a 0.01M HCl solution to prepare a pepsin solution with a concentration of 2 mg / ml; weighing SIS freeze-dried particles, pouring them into the pepsin solution and sealing them, placing them in a magnetic stirrer at room temperature and stirring them continuously for 24 hours until the solution becomes a homogeneous, clear, viscous, translucent SIS sol;
[0017] Optionally, the mass ratio of freeze-dried particles to pepsin is 10:1.
[0018] Porcine small intestinal submucosal extracellular matrix (SIS-dECM, hereinafter referred to as SIS) is a natural ECM material derived from pigs that has been processed by decellularization technology. It is also one of the most successfully applied animal-derived biomaterials. The biochemical composition and structure of SIS in hydrogel form are similar to those of complete biological scaffolds. After decellularization, SIS still retains bioactive molecules such as collagen, proteoglycans, glycosaminoglycans, adhesion and growth factors (such as transforming growth factor-b (TGF-b), basic fibroblast growth factor (b-FGF), vascular endothelial growth factor (VEGF)) and antimicrobial peptides. However, the poor mechanical properties, stability and degradation resistance of a single SIS material limit its application in colorectal anastomosis repair, so it is necessary to modify and modify it appropriately.
[0019] Optionally, the specific operation of preparing BA / SIS-SC hydrogel is:
[0020] The 2% SIS sol prepared in step (3) was adjusted to pH 7.0-8.0 and placed at 2-10°C for precooling; four-arm polyethylene glycol succinimidyl carbonate 4-ARM-PEG-SC powder (SC powder for short) was dissolved in a 5% boric acid-potassium chloride buffer solution with a pH of 7.5, and ultrasonically shaken for 3 minutes to prepare a SC solution, which was placed in a 4°C refrigerator for precooling for 10 minutes; after the precooling, the SIS sol and the SC solution were mixed evenly, and transferred to a 37°C constant temperature box or water bath for incubation for 3 minutes to obtain a BA / SIS-SC hydrogel.
[0021] Optionally, the mass ratio of the SIS sol to the SC solution is 2:1.
[0022] PEG is a hydrophilic polymer with good chemical stability, plasticity, metabolizability and biocompatibility. Compared with linear PEG, four-arm polyethylene glycol 4-ARM-PEG has more advantages in structure and function. Due to its multi-arm structure, 4-ARM-PEG not only has stronger terminal reactivity and higher modification flexibility, but also improves the cross-linking density, mechanical strength and chemical stability of hydrogels. (4-ARM-PEG-SC, referred to as SC) is a very useful cross-linking agent in material design and application. It can react with amine groups to form stable amide bonds, and the reaction is mild, efficient, stable and controllable. These reaction characteristics make SC very suitable for coupling proteins, peptides, drug molecules or other biomolecules, thereby realizing protein modification and functionalization. 4-ARM-PEG-SC is a PEG derivative grafted by 4-ARM-PEG and SC. Therefore, the application of 4-ARM-PEG-SC will greatly improve the cross-linking density of SIS hydrogels, further enhance mechanical properties and chemical stability, and protect the biological activity of SIS.
[0023] Boric acid-potassium chloride (BA-KCI) (hereinafter referred to as BA) buffer solution runs through the SIS-SC hydrogel system, which can kill most bacteria, fungi and viruses, and provide the hydrogel with the ability to resist bacteria.
[0024] The present invention also provides a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC, which is prepared by the above method.
[0025] The beneficial effect of the present invention is that the present invention uses boric acid-modified SIS and 4-ARM-PEG-SC as raw materials to prepare a multifunctional thermosensitive extracellular matrix hydrogel in the hope of achieving the effect of avoiding abdominal infection and preventing anastomotic leakage. A series of experiments show that the prepared hydrogel has a stable structure, good tissue adhesion and mechanical properties, excellent anti-explosion ability and self-healing properties, and its injectability can achieve effective closure of the anastomosis. In vitro experiments have shown that the hydrogel has good antibacterial properties and excellent cell and blood compatibility. This study provides new understanding and direction for the development of new multifunctional materials for the prevention and treatment of anastomotic leakage. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The adhesion (a) and bursting pressure (b) of the modified double-crosslinked thermosensitive extracellular matrix hydrogel of the present invention;
[0027] Figure 2 The figure is a rheological property diagram of the modified double-crosslinked thermosensitive extracellular matrix hydrogel of the present invention at 37°C with the change of angular frequency (0.1-100 rad / s);
[0028] Figure 3 The conductive performance test (a) and conductivity graph (b) of the modified double-crosslinked thermosensitive extracellular matrix hydrogel of the present invention;
[0029] Figure 4 This is a diagram showing the inhibitory effect of the modified double-crosslinked thermosensitive extracellular matrix hydrogel of the present invention on Staphylococcus aureus and Escherichia coli;
[0030] Figure 5 The biocompatibility test of the modified double-crosslinked thermosensitive extracellular matrix hydrogel of the present invention, wherein (A) is the effect of the hydrogel on the migration of mouse fibroblasts determined by scratching, (B) is the calculation of the migration rate, (C) is the live / dead fluorescent staining image, (D) is the quantitative cell survival rate, (E) is the cytotoxicity test of the hydrogel after co-incubation with fibroblasts for 1, 3, and 5 days, (F) is the blood compatibility of the hydrogel, and "+" and "-" represent the positive control and negative control, respectively;
[0031] Figure 6 This is a diagram showing the self-healing effect of the modified double-cross-linked thermosensitive extracellular matrix hydrogel of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] A method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC comprises the following steps:
[0034] (1) Preparation of SIS fragments: Select intestinal segments, cut them into pieces and sterilize them;
[0035] Select intestinal segments with complete intestines, uniform thickness and no lymph nodes, and cut them into intestinal segments about 10 cm long; use forceps to peel off the serosal layer and muscular layer, then turn the small intestine over so that the mucosa is outward, use a tongue depressor to repeatedly scrape the mucosal layer to expose the submucosal layer, and use forceps to remove larger tissue particles until no mucosal particles are visible to the naked eye; use sterile PBS buffer to rinse repeatedly to thoroughly remove tissues, cells and cell debris attached to the submucosal layer; cut the tubular submucosal layer along the longitudinal axis on a sterile table, and then use scissors to cut it into pieces <2 mm, soak it in a 20% ethanol solution containing 1.0% peracetic acid for 2 h for disinfection, soak it in a PBS solution containing 0.05% sodium azide for 2 h, and store it in a sterile PBS solution at 4°C for use.
[0036] (2) decellularizing and fragmenting the SIS fragments;
[0037] Place the chopped SIS fragments in a -80℃ refrigerator overnight, then place them on ice in a clean bench to reheat and dissolve, repeat twice; after complete dissolution, soak the SIS fragments in 0.1% sodium dodecyl sulfate PBS solution and shake to decellularize for 24 hours; then soak the SIS fragments in 1% DNase I and shake for 12 hours; prepare 1% CHAPS solution and use NaOH to adjust the pH to 7.2-7.4, soak the SIS fragments in CHAPS solution and wash for 48 hours; prepare 1% Triton X-100 solution, soak the SIS fragments in Triton X-100 solution and wash for 30 minutes to thoroughly wash away the cells, and finally rinse repeatedly with deionized water to remove residual reagents; the decellularized SIS fragments are placed in a freeze dryer and vacuum freeze-dried for 24 hours; after drying, the sample is placed in a freeze grinder and ground into powder to obtain SIS freeze-dried particles, and finally sterilized with ethylene oxide and stored in a -20℃ environment for use.
[0038] Alternatively, SIS fragments are soaked in 1% DNase I, SIS(v):DNase I(v)<1:2.
[0039] (3) Preparation of SIS hydrogel;
[0040] Pepsin was dissolved in 0.01M HCl solution to prepare a pepsin solution with a concentration of 2 mg / ml; SIS freeze-dried particles were weighed, poured into the pepsin solution and sealed, and placed in a magnetic stirrer at room temperature and stirred for 24 hours until the solution became a homogeneous, clear, viscous, translucent SIS sol;
[0041] Optionally, the mass ratio of freeze-dried particles to pepsin is 10:1.
[0042] (4) Preparation of BA / SIS-SC hydrogel.
[0043] The 2% SIS sol prepared in step (3) was adjusted to pH 7.0-8.0 and placed at 2-10°C for precooling; four-arm polyethylene glycol succinimidyl carbonate 4-ARM-PEG-SC powder (SC powder for short) was dissolved in a 5% boric acid-potassium chloride buffer solution with a pH of 7.5, and ultrasonically shaken for 3 minutes to prepare a SC solution, which was placed in a 4°C refrigerator for precooling for 10 minutes; after the precooling, the SIS sol and the SC solution were mixed evenly, and transferred to a 37°C constant temperature box or water bath for incubation for 3 minutes to obtain a BA / SIS-SC hydrogel.
[0044] Optionally, the mass ratio of the SIS sol to the SC solution is 2:1.
[0045] (1) Hydrogel has good adhesion and resistance to bursting pressure
[0046] Experimental method: The shear adhesion test of the hydrogel on the tissue was conducted on a universal tensile testing machine (Instron 5300, USA). Briefly, the pig small intestine was washed and cut into two pieces of 2cm×2cm and fixed on two glass slides. The hydrogel was evenly applied to the intestinal slices and tightly fitted, and then placed in a 37°C oven for incubation for 10 minutes. After the incubation, the glass slide was stretched horizontally and perpendicular to the hydrogel surface at a speed of 10mm / min on the universal tensile testing machine, and the tensile strength was recorded.
[0047] During the burst pressure test, a circular intestinal piece with a diameter of 2 cm was fixed on the test device, a 2 mm long incision was made on the intestinal piece, and 0.5 ml of BA / SIS-SC precursor solution was covered on the outside of the incision. After incubation at 37°C for 15 minutes, the device was started and the burst pressure was tested by injecting water at 5 ml / min. The peak pressure before the pressure loss was considered the burst pressure, and all experiments were repeated 3 times.
[0048] Results: Good tissue adhesion is the prerequisite for hydrogel to effectively prevent anastomotic leakage. Figure 1 As shown in (a), this embodiment uses an improved tensile test method to quantitatively determine the tissue adhesion of four hydrogels. Through testing, it was found that the tissue adhesion of the four hydrogels was 1.3±0.03Kpa, 4.93±0.02Kpa, 5.03±0.03Kpa, and 5.3±0.07Kpa, respectively. It can be seen that the introduction of SC greatly enhances the tissue adhesion of SIS hydrogel. As the mass fraction of SC in the hydrogel system increases, its adhesion gradually increases. This is attributed to the four active carbonyl groups (C=O) contained in the succinimide functional group in SC, which can react with the amino group (NH2) in the tissue to form a new and more stable amide bond, thereby forming a cross-linked network between the hydrogel and the tissue. The increase in the remaining succinimide groups increases the number of cross-links with the amino groups in the tissue, and the BA / SIS-SC hydrogel can firmly adhere to the surface of pig skin.
[0049] Studies have found that normal intestinal pressure is usually less than 8cm H2O, and the average intestinal pressure can reach 50cm H2O during colon obstruction. Figure 1The bursting pressure test device shown in (b) found that the bursting pressure of the four hydrogels was higher than the normal intestinal pressure, and even higher than the intestinal pressure during intestinal obstruction. As the SC mass fraction increased, the bursting pressure increased accordingly, which was consistent with the tissue adhesion measurement results. This anti-explosion ability allows our hydrogel to effectively block the fistula under high intestinal pressure, avoiding tissue corrosion caused by intestinal fluid overflow and abdominal infection caused by bacterial migration. When complicated by intestinal obstruction, under higher intestinal pressure, the hydrogel can still maintain the close fit and fixed position of the tissue wound, which is conducive to the healing and repair of the anastomosis.
[0050] (2) Hydrogel has good mechanical properties
[0051] Experimental method: The rheological properties of four hydrogels were tested using an advanced rotational rheometer (Malvern Kinexus lab+, England). First, four hydrogels with a diameter of 20 mm and a thickness of 1 mm were made in the same cylindrical mold according to the size of the rheometer base. During the test, the storage modulus (G′) and loss modulus (G″) of the hydrogel at 37°C were dynamically scanned with an angular frequency of 0.1 to 100 rad / s at a shear amplitude of 1% to analyze the mechanical strength of the material.
[0052] Results: The mechanical responsiveness of the four hydrogels was further analyzed using a rheometer within a certain angular frequency range (0.1-100 rad / s). Figure 2 As shown in the figure, at 37°C, the G′ of the two hydrogels is higher than G″, which indicates that the two hydrogels mainly exhibit elastic characteristics, which is conducive to the stability of their structure. Due to the addition of SC, the G′ of Gel 4 can reach 6.06Kpa, which is much higher than Gel 1 (0.6Kpa). This is due to the formation of amide bonds and double network structures, which greatly improves the structural stability and mechanical strength of BA / SIS-SC hydrogels, allowing the hydrogel to resist the pressure and intestinal wall movement in the intestine to a certain extent, and effectively support and close the anastomosis.
[0053] (3) Hydrogel is conductive
[0054] Methods: To evaluate the electrical conductivity of hydrogels, we placed SIS and BA / SIS-SC hydrogels in the same closed circuit for testing. Figure 3As shown in (a), two hydrogels, Gel 1 and Gel 4, of the same size (1.5 cm in diameter and 0.2 cm in thickness) were first synthesized in the same mold and cut into two halves. A power supply and a light-emitting diode (LED, 3 V, 20 mA) were connected to both ends of the hydrogel to form a closed circuit, and the brightness of the diode was observed to indicate the conductivity of the hydrogel. The hydrogel was then transferred to a conductivity tester (DDS-307, INESA) to quantitatively measure the conductivity of the two hydrogels.
[0055] Results: Figure 3 As shown in (b), through the conductivity test, we found that the LED lights up normally after the circuit is closed, indicating that both SIS and BA / SIS-SC hydrogels have good conductivity. Further conductivity tests found that the conductivity of the two hydrogels was 15.67±0.67mS / m and 17.67±0.88mS / m, respectively. This property enables BA / SIS-SC hydrogel to promote electrical signal conduction at the anastomotic tissue, regulate cell behavior, and promote anastomotic healing.
[0056] (4) Hydrogel has good antibacterial ability
[0057] Methods: The antibacterial ability of the hydrogels was tested using Gram-positive Staphylococcus aureus (ATCC.25923) and Gram-negative Escherichia coli (ATCC.25922). For all original bacterial solutions, a single colony of Staphylococcus aureus and Escherichia coli was first planted in 30 ml of Tryptone Soy Broth (TSB) and Luria-Bertani (LB) medium, respectively, and then incubated in a shaker (37 ° C, 200 rpm) for 12 h. The hydrogel precursor solution (1 mL each) was sterilized under UV light for 30 min, and four hydrogels were synthesized in a sterile environment and soaked in sterile PBS for 30 min. The four hydrogels were mixed with 6 ml of bacterial suspension (4×10 9 CFU / ml) were co-incubated at 37°C in a humidified environment for 10 h, and then 10 μl of the bacterial suspension after co-incubation (4×10 9 CFU / mL) were inoculated on agar plates (petri dishes) and cultured in a 37°C incubator for 24 hours. Finally, the CFU on the agar plates were counted and the antibacterial rate was calculated using the following formula:
[0058]
[0059] Results: The antibacterial ability of the four hydrogels was tested using standard strains of Gram-positive bacteria Staphylococcus aureus (S. aureus) and Gram-negative bacteria Escherichia coli (E. coli). Figure 4As shown in the figure, the four hydrogels showed significant inhibitory effects on both bacteria, and the colonies were significantly reduced compared with the control group. The antibacterial ability of Gel2-Gel4 against both bacteria was above 85%, which was much higher than that of Gel 1, and the inhibitory ability against Escherichia coli, the main bacteria in the intestine, was significantly stronger. However, with the increase of SC concentration, the antibacterial ability of Gel 2-Gel 4 did not change significantly, indicating that its antibacterial property mainly comes from BA / SIS. This is mainly due to the fact that the boric acid molecules in the hydrogel system bind to proteins such as membrane proteins, enzymes and signal molecules in bacteria, thereby destroying the bacterial cell wall and affecting bacterial growth and energy metabolism.
[0060] (5) Hydrogel has good biocompatibility
[0061] Methods: The cytocompatibility of hydrogels was tested using mouse L929 fibroblasts, as they are the main cell type in tissue repair. Gel 1 and Gel 4 were selected to represent SIS and BA / SIS-SC hydrogels, respectively. For the cell scratch test, 1 ml of each hydrogel precursor solution was first sterilized by ultraviolet light for 30 min and then mixed evenly in a sterile environment to form two hydrogels. The different hydrogels were soaked in 8 mL of DMEM culture medium for 12 h at 37 °C. The DMEM solution after co-culture was collected and filtered through a 0.22 μM membrane filter as the hydrogel extraction solution for cell scratch, proliferation, and live-dead experiments.
[0062] L929 cells were seeded in a 6-well plate and incubated with DMEM medium at 37°C for 24 hours. Cell scratches were made using a 10 μL sterile pipette tip. Sterile PBS was used to wash 3 times to remove floating cells. Hydrogel extract containing DMEM medium was added to the experimental wells for continued culture. The control group only added the same amount of DMEM medium. After incubation for 0h, 24h and 48h, the cell scratch images were observed using an optical microscope, and the cell migration rates of different groups were calculated using Image J software.
[0063] In order to observe cell proliferation, L929 cells were cultured at 5×10 3 The cells were seeded at a density of 100 μL / well in a 96-well plate and cultured with DMEM medium for 24 h before continuing to be cultured with hydrogel extract for 1, 3, and 5 days. The effect of hydrogel on cell proliferation was evaluated using the Cell Counting Kit-8. The samples on the 1st, 3rd, and 5th days were collected and incubated with 100 μL of fresh DMEM solution containing 10% CCK8 in a humidified incubator (37°C, containing 5% CO2) for 1 h, and the absorbance at 450 nm was measured using an ELISA reader.
[0064] In order to evaluate the cytotoxicity of the hydrogel, L929 cells were cultured at 3 × 10 4The cells were inoculated at a density of 100 μg / well in a 6-well plate and incubated at 37°C for 12 h, and then the hydrogel extract was added to continue incubation for 24 h. After the incubation, 2.5 μM calcein-AM and 2.5 μM ethidium homodimer solution were added and continued to incubate for 15 min for live cell-dead cell fluorescence staining. Fluorescence images were taken under an inverted fluorescence microscope. Based on the images obtained, the cell survival rate (ratio of live cells) was calculated using ImageJ software.
[0065] The hemolysis rate (HR) of Gel 1 and Gel 4 was tested using diluted blood containing 20% rat anticoagulant blood and 80% saline. Briefly, 200 μL of hydrogel precursor solution was injected into a 96-well plate to form a hydrogel. After washing three times with sterile saline, 1 ml of diluted rat blood (0.2 ml fresh anticoagulant blood + 0.8 ml saline) was added and incubated at 37°C for 1 hour. Blood (0.2 ml) diluted with only saline (0.8 ml) was used as a negative control, and blood (0.2 ml) diluted with only double distilled water (0.8 ml) was used as a positive control. After centrifugation at 1400 rpm for 5 minutes, the supernatant was taken and its absorbance at 545 nm was recorded using a microplate reader. The hemolysis rate calculation formula is as follows:
[0066]
[0067] Among them, OD hydrogel OD negative and OD positive Represent the measured absorbance of the hydrogel sample, negative control, and positive control, respectively.
[0068] Results: Previous series of experiments showed that Gel 2-Gel 4 had similar mechanical, adhesive and antibacterial properties, and all properties were significantly different from Gel 1. Therefore, only Gel 1 and Gel 4 were selected to represent SIS and BA / SIS-SC hydrogels, respectively, for biocompatibility testing. Figure 5 As shown in (A), the images of hydrogel extract and cells co-incubated for 24h and 48h were observed under a microscope and it was found that Gel 4 had the fastest cell proliferation rate. Figure 5 As shown in (B), by calculating the migration area, the migration rates of the control group, Gel 1 group and Gel 4 group cells at 24h were 20.47±0.97%, 34.88±0.63% and 43.87±1.78%, respectively; at 48h, the migration rates were 33.25±0.97%, 79.78±1.54% and 93.74±1.78%, respectively. This shows that BA / SIS-SC has a stronger ability to promote cell migration. Figure 5As shown in (C) and (D), live / dead staining experiments were further performed, and the quantitative cell survival rate of the three groups after 24 h of co-incubation showed that the cell survival rate of each group reached more than 98%, and there was no statistically significant difference. Figure 5 As shown in (E), the results of the CCK8 cytotoxicity experiment showed that the cells proliferated significantly in 1-5 days, and the number of cells in the Gel 1 and Gel 4 groups was more than that in the control group, and the difference was significant, proving that SIS and BA / SIS-SC have good cell compatibility. This is because the decellularized SIS and PEG groups themselves have excellent biocompatibility and non-immunogenicity, avoiding the occurrence of immune response. SIS can also promote the natural growth of cells by releasing growth factors. In addition, Gel 4 has a larger pore structure, which is conducive to the release of biomacromolecules and material exchange inside the hydrogel, and more effectively supports cell growth and differentiation.
[0069] For blood compatibility, such as Figure 5 As shown in (F), the hemolysis results showed that the hemolysis rates of Gel 1 and Gel 4 were 0.92±0.02% and 0.6±0.04%, respectively. All values were lower than the hemolysis value (2%) of the material specified in the International Organization for Standardization (ISO) 10993-4 standard, indicating that BA / SIS-SC does not undergo hemolysis.
[0070] (6) Hydrogel has self-healing properties
[0071] Methods: In order to analyze the self-healing property of BA / SIS-SC hydrogel at the macroscopic level, Gel 4 presols colored with two different dyes (red and green) were poured into two identical heart-shaped molds and incubated at 37°C for 10 min. The hydrogels of different colors were cut into two equal sections using a sterile scalpel, and the hydrogels of different colors were spliced along the incision and placed in an incubator for another 60 min. After the incubation, the hydrogels were taken out and cut into 0.5 mm thick slices along the coronal plane. The self-healing state of BA / SIS-SC was observed and recorded under an optical microscope.
[0072] In order to analyze the self-healing property of BA / SIS-SC hydrogel at the microscopic level, the rheological properties of Gel 4 hydrogel (cylinder with a diameter of 20 mm and a height of 1 mm) were tested using an advanced rotational rheometer and compared with Gel 1. The strain amplitude was scanned at a fixed 10 rad / s angular frequency to determine the gel-sol critical point of the hydrogel. The new hydrogel was replaced and the self-healing property of the hydrogel was characterized by alternating three cycles of large and small strains (small strain γ = 1%, interval 200 s; large strain γ = 50%, interval 300 s) at a fixed 10 rad / s angular frequency.
[0073] Results: To analyze the self-healing ability of BA / SIS-SC, macroscopic self-healing and oscillatory shear experiments were performed. Figure 6 As shown in the figure, the heart-shaped hydrogels of different colors were reassembled after cutting. After incubation for 120 minutes, a good self-repairing state was observed under a microscope at the splicing site of the hydrogel. The cutting line disappeared, and the two colors at the junction of the hydrogel merged with each other. The spliced hydrogel could effectively resist its own gravity. Its excellent self-healing performance is mainly attributed to the high active end of the succinimidyl ester, which allows the unreacted active groups to cross-link with the amino group again after the hydrogel structure is damaged to achieve self-repair. In addition, SIS-dECN contains a large amount of biomacromolecules such as collagen, glycosaminoglycans, and glycoproteins. It can self-assemble into gel through physical cross-linking such as hydrogen bonds and van der Waals forces. It has a certain dynamicity with the changes in temperature and pH, and can re-self-assemble and restore its three-dimensional structure within a suitable temperature and pH range.
[0074] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC, characterized in that: The steps include: (1) Preparation of SIS fragments: Select intestinal segments, cut them into pieces and sterilize them; (2) decellularizing and fragmenting the SIS fragments; (3) Preparation of SIS hydrogel; (4) Preparation of BA / SIS-SC hydrogel.
2. The method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC according to claim 1, characterized in that: In step (1), the specific operation of selecting the intestinal segments, cutting them into pieces and then sterilizing them is as follows: Select intestinal segments with complete intestines, uniform thickness and no lymph nodes, and cut them into intestinal segments about 10 cm long; use forceps to peel off the serosal layer and muscular layer, then turn the small intestine over so that the mucosa is outward, use a tongue depressor to repeatedly scrape the mucosal layer to expose the submucosal layer, and use forceps to remove larger tissue particles until no mucosal particles are visible to the naked eye; use sterile PBS buffer to rinse repeatedly to thoroughly remove tissues, cells and cell debris attached to the submucosal layer; cut the tubular submucosal layer along the longitudinal axis on a sterile table, and then use scissors to cut it into pieces <2 mm, soak it in a 20% ethanol solution containing 1.0% peracetic acid for 2 h for disinfection, soak it in a PBS solution containing 0.05% sodium azide for 2 h, and store it in a sterile PBS solution at 4°C for use.
3. The method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC according to claim 2, characterized in that: In step (2), the specific operation of decellularizing and fragmenting the SIS fragments is as follows: Place the chopped SIS fragments in a -80℃ refrigerator overnight, then place them on ice in a clean bench to reheat and dissolve, repeat twice; after complete dissolution, soak the SIS fragments in 0.1% sodium dodecyl sulfate PBS solution and shake to decellularize for 24 hours; then soak the SIS fragments in 1% DNase I and shake for 12 hours; prepare 1% CHAPS solution and use NaOH to adjust the pH to 7.2-7.4, soak the SIS fragments in CHAPS solution and wash for 48 hours; prepare 1% Triton X-100 solution, soak the SIS fragments in Triton X-100 solution and wash for 30 minutes to thoroughly wash away the cells, and finally rinse repeatedly with deionized water to remove residual reagents; the decellularized SIS fragments are placed in a freeze dryer and vacuum freeze-dried for 24 hours; after drying, the sample is placed in a freeze grinder and ground into powder to obtain SIS freeze-dried particles, and finally sterilized with ethylene oxide and stored in a -20℃ environment for use.
4. The method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC according to claim 3, characterized in that: Soak the SIS fragments in 1% DNase I, SIS(v):DNase I(v)<1:
2.
5. The method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC according to claim 4, characterized in that: In step (3), the specific operation of preparing SIS sol is as follows: dissolving pepsin in 0.01M HCl solution to prepare a pepsin solution with a concentration of 2 mg / ml; weighing SIS freeze-dried particles, pouring them into the pepsin solution and sealing them, placing them in a magnetic stirrer at room temperature and stirring them continuously for 24 hours until the solution becomes a homogeneous, clear, viscous, translucent SIS sol.
6. The method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC according to claim 5, characterized in that: The mass ratio of freeze-dried particles to pepsin was 10:
1.
7. The method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC according to claim 6, characterized in that: The specific operation of preparing BA / SIS-SC hydrogel is as follows: The 2% SIS sol prepared in step (3) was adjusted to pH 7.0-8.0 and placed at 2-10°C for precooling; the SC powder was pre-dissolved in a 5% boric acid-potassium chloride buffer solution with a pH of 7.5, and ultrasonically shaken for 3 minutes to prepare a SC solution, which was placed in a 4°C refrigerator for precooling for 10 minutes; after the precooling, the SIS sol and the SC solution were mixed evenly, and transferred to a 37°C constant temperature box or water bath for incubation for 3 minutes to obtain a BA / SIS-SC hydrogel.
8. The method for preparing a modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC according to claim 6, characterized in that: The mass ratio of SIS sol to SC solution was 2:
1.
9. A modified double-crosslinked thermosensitive extracellular matrix hydrogel BA / SIS-SC, characterized in that: Prepared by the method according to any one of claims 1 to 8.